Failure to Rescue after Infectious Complications in a Statewide Trauma System - Kaufman, Elinore J. (Surg Infect (Larchmt), 2017)
Background: The failure to rescue (FTR) rate, the rate of death after a complication, measures a center's ability to identify and manage complications by “rescuing” vulnerable patients. Infectious complications are common after trauma, but risk factors for death after infection are not established. We hypothesized that risk factors would differ for FTR after infectious complications, development of infections, and for development of and death after non-infectious complications. Patients and Methods: We analyzed trauma registry data for adult patients admitted to all 30 level I and II Pennsylvania trauma centers, 2011–2014. We used multivariable regression to identify risk factors for infection, non-infectious complications, failure to rescue after infection (FTR-I), failure to rescue after non-infectious complications (FTR-N), and death. We compared secondary complication patterns among patients with an index infection. Results: Of 95,806 admitted patients, at least one complication developed in 11.2%. Among these, 33.6% had an infection as the first complication. Mortality rates were 3.7% overall, 2.8% in patients with no complications, 7.2% after infection, and 13.5% after non-infectious complications. Urinary tract infection was the most common infection (41.7%), followed by pneumonia (37.5%) and wound infection (6.9%). Risk factors for infection included higher injury severity score (ISS), poor admitting physiology, female gender, cirrhosis, dementia, history of stroke, and drug abuse. Factors associated with FTR-I included male gender (odds ratio [OR] 1.6, 95% confidence interval 1.1–1.2), older age (OR 1.04, 1.03–1.05), increased ISS, cirrhosis, chronic renal insufficiency, and use of anticoagulation or steroids. Conclusions: Infectious complications are common in trauma patients and are an important component of FTR. Risk factors for infection and FTR-I differ and may help identify patients who may benefit from close surveillance and early intervention. Half of all FTR deaths were preceded by only a single complication, highlighting that management of this index complication, along with any secondary complications, may be a fruitful area for intervention.